2010
DOI: 10.1007/s12262-010-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prevention of Post-Operative Deep Vein Thrombosis [DVT] Using Nadroparin Among Patients Undergoing Major Abdominal Operations in India; a Randomised Controlled Trial

Abstract: Deep vein thrombosis [DVT] is one of the most dreaded complications in post-operative patients as it is associated with considerable morbidity and mortality. Majority of patients with postoperative DVT are asymptomatic. The pulmonary embolism, which is seen in 10% of the cases with proximal DVT, may be fatal. Therefore it becomes imperative to prevent DVT rather than to diagnose and treat. Only one randomized trial has been reported from India to assess the effectiveness of low molecular weight heparin in prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A prospective study done on major abdominal surgery patients from India reports negative incidence of DVT in both treatment and control arm. 10 Method used to detect DVT was lower limb venography. A trial from Tata Memorial Cancer Center was stopped prematurely due to nonincidence of DVT after examining 50 patients in prophylaxis group and 49 patients in control group.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study done on major abdominal surgery patients from India reports negative incidence of DVT in both treatment and control arm. 10 Method used to detect DVT was lower limb venography. A trial from Tata Memorial Cancer Center was stopped prematurely due to nonincidence of DVT after examining 50 patients in prophylaxis group and 49 patients in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients belonged to AJCC/TNM stage II and III, and all underwent curative resection. Two randomized controlled trials (RCTs) published from India showed negligible incidence of DVT after major abdominal and colorectal cancer surgery [13,14]. A RCT conducted to assess the risk of DVT in North Indian patients undergoing major abdominal surgery reported that none of the 65 patients Postoperative death (sepsis and multi organ failure) 1 (0.…”
Section: Discussionmentioning
confidence: 99%
“…A RCT conducted to assess the risk of DVT in North Indian patients undergoing major abdominal surgery reported that none of the 65 patients Postoperative death (sepsis and multi organ failure) 1 (0. 4 %) in two treatment arms developed DVT; Nadroparin prophylaxis was prescribed in 34 patients while 31 had no prophylaxis [13]. Another RCT performed at Tata Memorial Hospital was prematurely closed as none of the 99 colorectal cancer patients who underwent curative surgery (both prophylaxis and no prophylaxis group) were found to develop DVT [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations